2017
DOI: 10.1055/s-0043-117413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 5 Days of Sprint Training in Hypoxia on Performance and Muscle Energy Substances

Abstract: The present study was designed to determine the effect of 5 consecutive days of repeated sprint training under hypoxia on anaerobic performance and energy substances. Nineteen male sprinters performed repeated sprints for 5 consecutive days under a hypoxic (HYPO; fraction of inspired oxygen [FO], 14.5%) or normoxic (NOR; FO, 20.9%) condition. Before and after the training period, 10-s maximal sprint, repeated sprint ability (5×6-s sprints), 30-s maximal sprint, and maximal oxygen uptake (VO) tests were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…During the main experiment, the subjects conducted two exercise trials under either hypoxic (HYPO; F i O 2 , 14.5%, equivalent to a simulated altitude of 3,000 m) or normoxic (NOR; F i O 2 , 20.9%) conditions in a randomized order. The oxygen level of hypoxia was consistent with previous studies 24 25 26 . The study was completed with a single-blind, placebo-control design, and subjects were not given any information about the selected condition.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…During the main experiment, the subjects conducted two exercise trials under either hypoxic (HYPO; F i O 2 , 14.5%, equivalent to a simulated altitude of 3,000 m) or normoxic (NOR; F i O 2 , 20.9%) conditions in a randomized order. The oxygen level of hypoxia was consistent with previous studies 24 25 26 . The study was completed with a single-blind, placebo-control design, and subjects were not given any information about the selected condition.…”
Section: Methodssupporting
confidence: 92%
“…Growing attention has been paid to the efficacy of maximal sprint training under hypoxia among athletes 4 6 9 10 11 12 13 14 16 19 20 24 25 26 . Among them, several studies have revealed that repeated sprint training in hypoxia (RSH) causes further improvement in repeated sprint ability (RSA) in various types of male athletes (e. g., team-sport athletes, cyclists, cross country skiers) 4 6 9 11 12 13 16 20 24 .…”
Section: Introductionmentioning
confidence: 99%
“…A 5–10 min rest period was inserted between components. The above protocol was designed to improve anaerobic power output in 100–200 m track and field sprinters; we previously confirmed that the training increases 10-s maximal power output and repeated sprint ability [ 26 ]. Environmental conditions during the exercise session were controlled at 22 °C and 40% humidity.…”
Section: Methodsmentioning
confidence: 99%
“…One previous study reported that performance during a single Wingate effort improved when assessed 9 days but not 2 days after the hypoxic training intervention (Hendriksen and Meeuwsen, 2003). Two other studies using trained sprinters reported that 5 to 6 consecutive days of hypoxic training composed of RW (repeated maximal sprints of 15-30 s) and repeated sprint training (repeated maximal 6-s sprints) failed to induce improvement in single Wingate effort 3 days after the intervention (Kasai et al, 2017(Kasai et al, , 2019. Since performance was not assessed in the first few days or several weeks after the intervention, immediate and long-term consequences of our intervention are unknown.…”
Section: Performance Outcomesmentioning
confidence: 98%